2005
DOI: 10.1002/dac.741
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing user-perceived impairment events using end-to-end measurements

Abstract: SUMMARYMeasures of quality of service (QoS) must correlate to end-user experience. For multimedia services, these metrics should focus on the phenomena that are observable by the end-user. Metrics such as delay and loss may have little direct meaning to the end-user because knowledge of specific coding and/or adaptive techniques is required to translate delay and loss to the user-perceived performance. Impairment events, as defined in this paper, are observable by the end-users independent of coding, adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It was shown that the method from [1] results in a reasonably accurate MMPP model for medium sized traces. However, this method may not be very accurate when there is a need to model longer traces that exhibit diurnal traffic variations [4]. In this paper we modify the method proposed in [1] and show, using several 24 hour traces, that the new method provides a better model for longer traces at the expense of an increased number of states.…”
mentioning
confidence: 99%
“…It was shown that the method from [1] results in a reasonably accurate MMPP model for medium sized traces. However, this method may not be very accurate when there is a need to model longer traces that exhibit diurnal traffic variations [4]. In this paper we modify the method proposed in [1] and show, using several 24 hour traces, that the new method provides a better model for longer traces at the expense of an increased number of states.…”
mentioning
confidence: 99%